Crack identification in beam-type structural elements using a piezoelectric sensor. Issue 6 (2nd November 2021) - Roy, Goutam; Panigrahi, Brajesh; Pohit, G.
ABSTRACT: A crack or any kind of damage induces a sharp discontinuity in the rotational displacement curve in a structure under load. However, if the beam is not loaded sufficiently or crack depth is very small, the discontinuity may not be possible to identify through conventional methods. This study proposes a non-destructive approach to reveal the presence of a crack in structural components based on the measurement of very small discontinuity in rotational displacement by employing a piezoelectric sensor (PZT). An analytical model of a statically loaded cracked beam with PZT attached to the beam is developed for various boundary conditions. The solution is obtained through Ritz approximation. Rotational displacements at different points along the length of the beam are determined. Subsequently, a finite element analysis on ABAQUS platform is carried out for comparison. The results obtained from these analyses are validated with the experimental data published in open literature. Two distinct techniques are employed to monitor the damage in slender and short length beams. the efficacy of the technique in the detection of small cracks in structure is established. It is also shown that the presence of multiple cracks in beams having various boundary conditions can be monitored by a single non-destructive investigation following the method.